Peran Cinta dalam Teologi Moral - Agustinus Abraham (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Love plays a central role in Christian moral theology as the fundamental principle guiding human moral decisions and actions. This study aims to examine the meaning, concept, and role of love in moral theology, as well as its practical application in Christian life. Employing a qualitative method with a literature review approach, this research explores theological perspectives, Scriptural foundations, and the moral implications of love within the Christian tradition. The findings show that moral theology is inseparable from the nature of God as Love, and that love is not merely an emotion but a deliberate moral act oriented toward the good of others. Christian love, understood as agape, represents the highest form of selfless and sacrificial love and becomes the normative basis for moral judgment. Love gives meaning and value to human moral actions, shapes ethical principles, and directs believers to live according to God’s will. In moral practice, love enables Christians to act justly, uphold human dignity, and build harmonious relationships with God, others, society, and creation. The study implies the need for strengthening love-based moral formation within the Church and society, especially amid modern challenges and the growing distortion of love among young people. Future research is recommended to expand on interdisciplinary studies and contextual applications of love in various socio-cultural and religious settings.